Evalution of energy for bioethanol production - Bánszki, Lívia; Rátonyi, Tamás; Harsányi, Endre (Acta Agraria Debreceniensis, 2013)
The objective of this study was the ethanol which classified as agro fuels. The aim of our research was the calculation of efficiency of bioethanol production, and evaluates the yield of maize hybrids grown for this purpose. We examined the energy demand of corn production per hectare in two vintages of 2009 and 2010. The focus of the experiment was placed in three different doze of fertilizer. Results show that the control corn plot used the least amount of non-renewable energy. Improving starch yield by adding fertilizer required additional nonrenewable energy inputs. So then the invested energy has a great impact on the efficiency.